2021
DOI: 10.3390/ijerph18094524
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Characteristics of Environmental Air Quality and Its Relationship with Seasonal Climatic Conditions in Eastern China during 2015–2018

Abstract: Exploring the relationship between environmental air quality (EAQ) and climatic conditions on a large scale can help better understand the main distribution characteristics and the mechanisms of EAQ in China, which is significant for the implementation of policies of joint prevention and control of regional air pollution. In this study, we used the concentrations of six conventional air pollutants, i.e., carbon monoxide (CO), sulfur dioxide (SO2), nitrogen dioxide (NO2), fine particulate matter (PM2.5), coarse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study in Lanzhou, China (the same area as this study) from 2001 to 2005 showed that the average concentration of SO 2 was 79.09 μg/m 3 and total RD hospital admissions were significantly increased by 3.4% (RR = 1.034, 95% CI 1.002, 1.067) per inter-quartile range increase in SO 2 (Tao et al, 2014 ). Comparing Tao’s study (Tao et al, 2014 ) with this study, the mean concentrations of SO 2 during different periods showed a decrease, mainly attributable to the large-scale deployment of flue gas desulfurization at China’s power plants (Wang et al, 2014 ), the strict control of SO 2 industrial emissions (Wang et al, 2021 ), innovation in engine technology and the use of clean fuels. Evidence from Wuhan also showed that cleaner fuel with a lower SO 2 levels has been associated with substantial reductions in respiratory morbidity (Wang, 2017 ).…”
Section: Discussionmentioning
confidence: 50%
“…A study in Lanzhou, China (the same area as this study) from 2001 to 2005 showed that the average concentration of SO 2 was 79.09 μg/m 3 and total RD hospital admissions were significantly increased by 3.4% (RR = 1.034, 95% CI 1.002, 1.067) per inter-quartile range increase in SO 2 (Tao et al, 2014 ). Comparing Tao’s study (Tao et al, 2014 ) with this study, the mean concentrations of SO 2 during different periods showed a decrease, mainly attributable to the large-scale deployment of flue gas desulfurization at China’s power plants (Wang et al, 2014 ), the strict control of SO 2 industrial emissions (Wang et al, 2021 ), innovation in engine technology and the use of clean fuels. Evidence from Wuhan also showed that cleaner fuel with a lower SO 2 levels has been associated with substantial reductions in respiratory morbidity (Wang, 2017 ).…”
Section: Discussionmentioning
confidence: 50%
“…Subgroup analysis was conducted in BMI-stratified subgroups (baseline characteristics shown in Table S2 ( supplementary material ), which were classified as underweight (n=25,821), normal (n=146,081), overweight (n=18,187), obese (n=3,372). PM 2.5 was divided into four specific groups with an interval of about 40 μg/m 3 based on the air quality index (AQI) derived from a four-year (January 2015-December 2018) EAQ data of Eastern China (EC) ( 9 ). In each subgroup, mean values (± 2SE, standard error) of birthweight were calculated at four PM 2.5 groups of the whole pregnancy and demonstrated in a broken-line graph ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of macrosomia in China was 6.9% in 2007-2008, and ranged from 7.3% to 8.7% in 2010-2014, higher than the average of 23 lowincome and middle-income countries (5,6), while the incidence of low birthweight in babies (≥28 gestational weeks) was unchanged between 2012-2018 at around 5.5% (5). Birthweight is closely related to intrauterine environment, whose establishment is rooted in multi-factorial interactions including maternal metabolic status, genetic expression, life style, and also physical environment (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, with this rapid economic growth [2], the coal-dominated energy structure and extensive economic development have led to excessive consumption of resources and aggravated environmental and ecological damage [3,4]. Air pollution, one of the most prominent environmental problems at present [5], has exerted a series of negative impacts on human health [6], social harmony and stability [7], and sustainable economic growth [8]. In response to this problem, the Chinese government has enacted a series of laws and regulations to oversee the conduct of all walks of life, protect and improve the atmospheric environment, and advance the construction of an ecological culture.…”
Section: Introductionmentioning
confidence: 99%